Adoção de crianças e adolescentes com necessidades especiais: aspectos psicossociais envolvidos - SILVA, Fabíola Helena Oliveira Brandão da (Universidade Federal do Pará, 2019)
This study aimed to understand and describe the psychosocial aspects of adoption of children and adolescents with special needs since the creation of the National Register of Adoption (NRA), in April 2008. Thus, we set out goals that motivated the development of the three constituents of the dissertation studies. The first described the social and family demographic characteristics of applicants for adoption to parents of children with and without typical development. Furthermore, drew a profile of children and adolescents considered suitable for adoption, enrolled in CNA. The second study aimed to investigate risk factors and protective for the development of three adopted children with special needs, analyzing common and unique aspects of their life histories, since the psychosocial condition of the biological parents to the process of entering and living in the family replacement. The third involved three families who have adopted children with special needs, who had prior knowledge of this infantile condition, in order to describe the familiar routines. From the results obtained by the three studies was possible to know the sociodemographic characteristics and aspects of structure and family dynamics that mark in general, and in particular in the cases studied, the demands generated by children with special needs and how applicants and parents by adoption have undertaken to answer them. We conclude that both candidates to the adoption of children with special needs, as their adoptive parents appeared to favor the fulfillment of children's demands, especially family life provide these children in vulnerable.